PENDIDIKAN AGAMA ISLAM BAGI ANAK PUTUS SEKOLAH DI DESA KASIRO ILIR KECAMATAN BATANG ASAI KABUPATEN SAROLANGUN - Wulandari; Rasidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of Islamic Religious Education (PAI) for school dropouts in Kasiro Ilir Village, Sarolangun Regency, along with the dynamics of influencing factors and the teaching strategies applied by educators. The high dropout rate caused by economic constraints has prompted community leaders to initiate non-formal religious education to prevent moral decadence among adolescents. This research employs a descriptive qualitative approach. Field data were collected through observation and in-depth interviews with local clerics (ulama), Quran teachers, parents, and school dropouts. The data were then analyzed through data reduction, data display, and conclusion drawing, utilizing source triangulation techniques for validity. The findings reveal that PAI is implemented flexibly at the teacher's residence by adopting classic Islamic boarding school (pesantren) methods, namely sorogan, bandongan, and talaqqi. The learning materials focus on Quranic literacy and the study of classic Islamic texts (kitab kuning) to instill essential moral values. The sustainability of this program is heavily supported by the high dedication of the educators and the cultural support of the local community, although it is still hindered by inadequate facilities, the fluctuating learning motivation of the children, and the absence of government intervention. Overall, the familial approach applied by the teachers has proven to be crucial and effective in restoring the religious understanding and character of children who are marginalized from the formal education system.